(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
research deals with the study of the effect of annealing during and after deposition on the optical and structural properties for zinc sulfide (ZnS) films prepared on Soda glass bases under pressure (10^(-5) torr) by vacuum thermal evaporation method. Then studying the crystal growth of thin films through the results have been obtained, where the optical properties were studied during deposition by taking temperatures ((50°C, 100°C, 150°C, 200°C) for an hour and after depositing annealing at temperatures (R.T, 250°C, 300°C, 350°C) using a spectrometer from Type (UV-Visible). It has been found during deposition that the transmittance increases oscillating correspondingly with the increase in the wavelength of the photon while it increases more oscillatory so that the transmittance eV (68,75,82,88) corresponding to the temperature (R .T,250°C, 300°C,350°C ). The energy gap decreased from eV (3.7,3.65,3.63,3.6) corresponding to temperatures (200°C,150°C,100°C,50°C) to eV (3.44,3.45,3.47,3.48) corresponding to temperatures Temperature (350°C, 300°C, 250°C, R.T after annealing.